Structural Modifications of 3-Triazeneindoles and Their Increased Activity Against Mycobacterium tuberculosis - Konstantin B. Majorov; Boris V. Nikonenko; Pavel Yu. Ivanov; Lyudmila N. Telegina; Alexander S. Apt; Valeria S. Velezheva (MDPI AG, 2020)
We synthesized 100 novel indole-based compounds with polyaza-functionalities, including 3-triazeneindoles, and tested their activity in vitro against laboratory M. tuberculosis H37Rv and clinical izoniazid-resistant CN-40 isolates, using gross and fine titration approaches. Here we present a few 3-triazeneindoles with the highest anti-mycobacterial activity. Introduction of short lipid tails into the 3-triazeneindole core additionally increased their activity against mycobacteria engulfed by murine macrophages. We also demonstrate that the compound TU112, one of the most active in our previous study, being not bioavailable after administration in mice per os, manifests prominent anti-mycobacterial activity after intravenous or aerosol delivery, as assessed by the mouse serum and lung supernatant titration assays.